Biomethane Production as an Alternative Cooking Energy Source in Jakarta - ., Diyono (Rekayasa Material, Manufaktur dan Energi, 2024)
This study delved into the viability of biomethane as a cleaner alternative to fulfil Jakarta's substantial cooking energy needs, which is currently reliant on liquid petroleum gas (LPG). By harnessing waste streams from wastewater, organic waste, and crop residues in an anaerobic digester, biogas was produced and subsequently upgraded into biomethane. Sodium hydroxide (NaOH) was utilized to enhance biogas production efficiency. Biomethane production amounted to 1.58 million tons annually, covering approximately 68.74% of the cooking energy demand. Although this falls short of Jakarta's annual LPG demand of 2.88 million tons, the study proposes a distribution scheme to bridge this gap and facilitate the broader adoption of biomethane. This research underscores the potential of biomethane in reducing LPG dependency, offering promising avenues for sustainable urban energy solutions.